Mineral Resources Exploitation of Yakutia in the 1920s Programs Development - N. I. Burnasheva; I. I. Kovlekov (Научный диалог)
The article is devoted to the development of an industrial policy for the development of natural mineral resources of Yakutia, the main provisions of which were approved in 1927 at the V All-Yakut Congress of Soviets. The relevance of the study of the industrial policy of the 1920s is related to the fact that many approaches to the issues of planning and organizing production later proved themselves, turning into certain practical production results. The article describes the experience of Yakutia in the development of a prospective regional plan. It is based on the principles of economic zoning taking into account the peculiarities of the economy of certain regions of the country and combining the requirements of the Center with the capabilities of the regions. The basis of the industrial policy of Yakutia made up plans for the primary development of the mining industry and the gold mining industry, which were to form the basis for the development of the national economy, the mining and processing local industry, the agricultural production, transport and communications. It was concluded that the development of industrial policy based on economic regionalization allowed Yakutia to take the first steps to integrate the economy into the all-Russian economic development plan and into the process of socialist reconstruction of the country's economy, to determine its place in the division of labor, to identify its economic specificity and specialization.